An Assay of the Antithrombotic Action of Warfarin: Its Correlation with the Inhibition of Stasis Thrombosis in Rabbits - Wessler, Stanford; Gitel, Sanford N; Bank, Harry; Martinowitz, Uri; Stephenson, Ronald C (Thrombosis and Haemostasis, 1978)
No assay of the antithrombotic action of warfarin has been available. Experiments were performed to determine whether Xa inhibitory activity - the reaction rate between activated factor X (Xa) and antithrombin III - could serve this function. 105 warfarin-treated patients demonstrated a significant 18% increase in Xa inhibitory activity compared to 51 controls, p <0.001, without any correlation between this activity and the prothrombin times in the treated patients. A similar increase in Xa inhibitory activity was obtained in rabbits treated with 2 mg of warfarin per day compared to control animals, p <0.001. Employing an assay which routinely produced venous thrombosis after clotting proteases were infused into warfarin-treated and control rabbits, three observations were made. 1. The extent of stasis thrombosis induced by injection of thrombin, Xa or activated factor IX, was significantly reduced in warfarin-treated rabbits compared to control animals, independent of alteration in the four established vitamin K-dependent zymogens. 2. In the rabbit, significant changes in prothrombin times and prothrombin and factor X activities preceded by 5 days both the increase in Xa inhibitory activity and the antithrombotic effect which became significant on the sixth day. 3. The correlation between Xa inhibitory activity of warfarin-treated rabbits and the extent of stasis thrombosis induced by Xa was significant, p<0.05. Xa inhibitory activity is one measure of the antithrombotic action of warfarin.